Membangun Kesadaran Hak Cipta dalam Praktik Karya Siswa melalui Pendekatan Sosiologi Hukum di SMAN 1 Sekotong, Lombok Barat - Tata Eliestiana Dyah A; Jamaludin Jamaludin; Heru Sunardi; Andi Mulyan; Yuda Martadinata (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2026)
This community service activity aimed to strengthen students’ legal awareness of copyright in the use of digital works within the school environment. The activity was conducted at SMAN 1 Sekotong, West Lombok, by applying a sociology of law approach so that copyright was not merely understood as a normative legal rule, but also as part of students’ everyday academic practices. The activity was carried out through legal socialization, case discussions, citation practice, introduction to moral and economic rights, and reflection on students’ habits in using texts, images, music, videos, designs, and other digital materials from the internet. The results indicate that some students initially perceived the use of other people’s works as a common academic habit, especially when such works were easily accessible online. After the activity, students began to understand that easy access does not eliminate legal protection over copyrighted works. They also showed improved understanding in distinguishing quotation, paraphrasing, inspiration, plagiarism, and the use of works that may potentially infringe copyright. This activity affirms that copyright education in schools should be practical, participatory, and closely connected to students’ real experiences in order to foster an honest, ethical academic culture that respects intellectual works.